The Bush Foreign Policy 2001-2003: Unilateralist Theory in a Multilateral World, and the Opportunity for Change Offered by Iraq - Michael J. Kelly (Washington University Global Studies Law Review, 2003)
It should come as no surprise that George W. Bush arrived in Washington in 2001 with the unilateralist approach to politics that got him twice elected governor of Texas, secured the Republican nomination, and paved his path to the White House. Thus, from his point of view, there was no good reason to abandon it upon moving into the Oval Office. No matter that it delighted only his political base and alienated everyone else, inside and outside the G.O.P. It should also come as no surprise, therefore, that this political attitude lapped over into the foreign policy arena as a natural outgrowth of President Bush’s basic philosophy. Such a simplistic, straightforward approach is certainly attractive, and easily sold to like-minded conservatives on whom the President relies heavily for political support; but it is unpersuasive in the arena of foreign relations and ineffective in the conduct of long-term foreign policy.
Keywords: Foreign policy; International; Iraq; United States